Psoriasis and gut microbes: research advances from mechanism to therapy - Chen, Jianfei; Sun, Keyun; Zhang, Xinyu; Chen, Xiaojie; Chu, Yunning; Geng, Limin; Bian, Ziwen; Su, Yang; Cong, Xuefei; Wang, Guoli (Frontiers in Microbiology, 2025)
BackgroundPsoriasis is a chronic, immune-mediated, relapsing inflammatory skin condition, with its pathogenesis remaining incompletely understood and clinical eradication presenting significant challenges. Recent studies have highlighted the role of gut microbiota in psoriasis pathogenesis, emerging as a focal point of research.ObjectiveThis review aims to systematically elucidate the core mechanisms by which gut microbiota contribute to psoriasis pathogenesis, summarize advances in gut microbiota-based therapeutic strategies, and provide theoretical support and innovative insights for both basic research and clinical treatment of psoriasis.MethodsComprehensively retrieve and analyze recent research literature on the gut microbiota characteristics of psoriasis patients, the regulatory mechanisms of the gut-skin axis, and related therapeutic interventions, focusing on the microbiota’s effects on immune modulation, intestinal barrier integrity, and metabolic products.ResultsAccumulating evidence supports a complex, bidirectional regulatory relationship between gut dysbiosis and skin inflammation, with notable alterations in the diversity and relative abundance of gut microbial communities in patients with psoriasis compared to healthy individuals. This review comprehensively examines the mechanisms through which gut microbes contribute to psoriasis development via the gut-skin axis, influencing immune regulation, intestinal barrier integrity, and related metabolites. Additionally, the potential of gut microbiota-based therapies—such as oral probiotics, prebiotics, synbiotics, and fecal microbiota transplantation—in alleviating psoriasis symptoms and reducing disease recurrence is emphasized.ConclusionDysbiosis of the gut microbiota is a key factor in the pathogenesis of psoriasis. The regulatory mechanisms of the gut-skin axis offer new insights into the multisystemic associations of psoriasis. Gut microbiota-based therapeutic strategies hold promise as important adjuncts to conventional treatments, laying the foundation for developing novel targeted therapies. This approach carries significant clinical implications for improving the prognosis of psoriasis patients.